On Semipolygroups - Wannusit, Sutasinee; Patthanangkoor, Poonchayar (Thai Journal of Science and Technology, 2018)
Abstract In this paper, we introduce the notions of semipolygroups and (strongly) regular relation, and investigate their basic properties. Moreover, we review the concepts of polygroups and some of their properties are also described. Keywords: semipolygroup; (strongly) regular relation; polygroup